Silver‐Nanoparticle‐Embedded Short Amphiphilic Peptide Nanostructures and Their Plausible Application to Reduce Bacterial Infections. (19th January 2023) - Kumar Tripathi, Satyendra; Kesharwani, Khushboo; Saxena, Deepanshi; Singh, Ramesh; Kautu, Aanand; Sharma, Shruti; Pandey, Archna; Chopra, Sidharth; Ballabh Joshi, Khashti
Abstract: The microbiota‐gut‐brain axis (GBA) plays a critical role in the development of neurodegenerative diseases. Dysbiosis of the intestinal microbiome causes a significant alteration in the gut microbiota of Alzheimer's disease (AD) patients, followed by neuroinflammatory processes. Thus, AD beginning in the gut is closely related to an imbalance in gut microbiota, and hence a multidomain approach to reduce this imbalance by exerting positive effects on the gut microbiota is needed. In one example, a tyrosine‐based short peptide amphiphile (sPA) was used to synthesize antibacterial AgNPs−sPA nanostructures. Such nanostructures showed high biocompatibility and low cytotoxicity, and therefore work as model drug delivery agents for addressing local bacterial infections. These may have therapeutic value for the treatment of microbiota‐triggered progression of neurodegenerative diseases. Abstract : We designed and developed short peptide amphiphile‐based silver nanosystems with antimicrobial properties. These lipidated peptides are nontoxic toward healthy eukaryotic cells, thereby showing high biocompatibility. Such silver‐nanoparticle‐embedded tyrosine‐based short peptide amphiphile nanostructures have potential therapeutic value for the treatment of microbiota‐triggered progression of neurodegenerative diseases.